169k views
2 votes
Perform the indicated operation.
h(x) = 3x - 1
g(x) = 2x – 4
Find (hog)(x)

Perform the indicated operation. h(x) = 3x - 1 g(x) = 2x – 4 Find (hog)(x)-example-1
User Galarant
by
4.8k points

2 Answers

6 votes
h(g(x)
h(2x-4)
3(2x-4)-1
6x-12-1
6x-13=(hog)(x)
User Vladimir Sidorenko
by
5.4k points
1 vote

Answer:


\large\boxed{(h\circ g)(x)=6x-16}

Explanation:


h(x)=3x-1\\\\g(x)=2x-4\\\\(h\circ g)(x)=h\bigg(g(x)\bigg)\\\\\text{Substitute instead of x the expression (2x - 4) to h (x):}\\\\(h\circ g)(x)=3(2x-4)-4\qquad\text{use the distributive property}\\\\(h\circ g)(x)=(3)(2x)+(3)(-4)-4\\\\(h\circ g)(x)=6x-12-4\\\\(h\circ g)(x)=6x-16

User Goodnesskay
by
5.6k points